Implicações do uso de gifs animados, boomerangs, cinemagraphs e produtos audiovisuais para a fotografia na publicidade - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work intends to reflect about the implications of the uses of animated GIFs, boomerangs, cinemagraphs and audiovisual products for photography in advertisement. For this, it establishes two moviments: the panoramic and the trigger. In the panoramic, it reviews the concepts of animated GIF (CAMPOS, 2017), boomerang (GOOGLE PLAY, 2018), cinemagraph (DESIGN CULTURE, 2017) (FLIXEL, 2018a; 2018b) and audiovisual product (MACHADO, 2011). In the trigger – which reflects, in essay tone, about restlessness – it uses Flusser (1985), Covaleski (2010), Santaella (2011), Barthes (2017), Benjamin (1994) and Sontag (2004). This moviment is separated in three triggers that act stimulating the reflection: the first one points out similarities and differences between the uses of photography and the uses of technical images, to understand in which they approach and in which they differ; the second intends to reflect if advertisement only does Studium and, therefore, answer in a direct way if Punctum can be present in advertisement‘s photography; and the third one reflects on what can be peculiar in photography. The method that builds this research is bibliographic, and because it‘s reflexive, can be considered purely qualitative. At last, the paper finds interesting to rethink the role of photography in advertisement.
Keywords: Fotografia; Fotografia - Técnicas digitais; Publicidade; Processamento de imagens - Técnicas digitais; Comunicação; Redes sociais on-line; Photography; Photography - Digital Techniques; Publicity; CNPQ::CIENCIAS SOCIAIS APLICADAS